Cellulose fiber and product using same

By controlling the aggregation of cellulose nanofibers and the microrefining treatment of cellulose, and using solvent replacement and electrospinning, cellulose microfibers with uniform fiber diameter distribution and low proportion of coarse structures were prepared, which solved the problem of cellulose nanofiber aggregation blocks and achieved efficient microrefining and low-cost production.

CN119855946APending Publication Date: 2025-04-18ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380065028.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-14
Filing Date
2023-10-11
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem that cellulose nanofibers are prone to form aggregates during storage, stirring and drying, resulting in increased viscosity and increased processing difficulty, and it is difficult to completely fine-fine cellulose raw materials without using mechanical and chemical treatment.

Method used

By controlling the aggregation of cellulose nanofibers, the residue of the unmilled part of the raw material cellulose and the bonding between the fibers, solvent replacement and electrospinning are used to prepare cellulose microfibers, which have uniform fiber diameter distribution and low proportion of coarse structures.

Benefits of technology

The uniformity and efficient microfiber of cellulose microfibers are achieved, the formation of agglomerates is avoided, the production cost is reduced, and the biodegradability of cellulose is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855946A_ABST
    Figure CN119855946A_ABST
Patent Text Reader

Abstract

Provided are cellulose microfibers (fibrous cellulose) which have a uniform fiber diameter distribution in which the proportion of both cellulose nanofibers and coarse structures is low and which can be widely used in various applications, a composition containing the cellulose fibers, and a porous body formed from the cellulose fibers. The present invention pertains to a cellulose fiber having an average fiber diameter of 0.3-3.0 [mu] m (inclusive) in a dry state as observed by an electron microscope, the proportion of fibers having a fiber diameter of less than 0.1 [mu] m being 5% or less, and the proportion of coarse structures being 3.0% or less, the ratio of the thick structures is an index of the ratio of the number of fibers having a Wet fiber diameter of 20 [mu] m or more as measured by optical automatic analysis. The present invention also relates to a composition comprising the cellulose fiber, and a porous body formed from the cellulose fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to cellulose fibers and products using the cellulose fibers. Background Art

[0002] Cellulose is the most abundant carbohydrate on earth, a natural and biodegradable resource, and is used in various industrial fields. Furthermore, with the formulation of SDGs (Sustainable Development Goals) in recent years, it is expected to be a sustainable resource with low environmental impact.

[0003] As one of the effective methods of utilizing cellulose, cellulose nanofibers obtained by micronizing cellulose have attracted attention. As a method of utilizing cellulose, there are various uses such as fillers of resins and rubbers, transparent materials of electronic products, substrates of optical materials, filter materials, additives of foods, coatings, cosmetics, packaging materials, substrates of gas barrier materials, viscosity modifiers of various liquid products, dispersion stabilizers, etc., and cellulose nanofibers corresponding to the required performance have been studied. By combining the selection of the type of cellulose as a raw material, the selection of physical micronization conditions, the selection of chemical treatment conditions, etc., nanofibers of cellulose raw materials with various shapes and characteristics can be obtained.

[0004] On the other hand, the aggregation effect based on intermolecular force of cellulose nanofiber is strong, and it is not only easy to produce aggregates due to aggregation during storage, and the generation of aggregates accompanied by strong hydrogen bonds during drying, but also easy to produce aggregates due to the entanglement of fibers during stirring and mixing. Furthermore, when treated as a slurry, the viscosity becomes too high, and sometimes it is difficult to handle. And then, the micronization requires strong mechanical treatment and the treatment using chemicals, and the cost becomes high. From these aspects, in the use that does not require nanofibers, it is sometimes used in the form of microfibers with weakened micronization force.

[0005] However, if the force of the pulverization is weakened, the original cellulose raw material cannot be pulverized completely, and an unpulverized portion remains. If the force of the pulverization is strengthened in order to reduce the unpulverized portion, a portion of the cellulose is converted into nanofibers, and aggregates are generated.

[0006] Aggregates resulting from such aggregation of nanofibers and unbroken portions that cannot be fined are coarse structures that are greatly different from the fiber structure having an L / D within a certain range, and may impair the original performance of microfibers depending on the application.

[0007] For example, in the following Patent Document 1, cellulose nanofibers are subjected to oxidation treatment and then mixed with rubber latex to obtain a filler-rubber composite. The coarse structures in the rubber obtained by making the latex high in viscosity are intended to be reduced, but as described in the examples, the rubber masterbatch contains a considerable amount of coarse structures of 10 μm or more in a dry state. It is speculated that the reason is due to the generation of aggregates caused by the aggregation and entanglement of nanofibers.

[0008] In the following patent document 2, a cellulose raw material with a small amount of hemicellulose components is wet-milled to obtain cellulose microfibers. The fiber diameter is adjusted under the conditions of wet milling, but in the process of micronization by milling, it is impossible to avoid either nanofibrillation or the residue of the unmilled portion or both, and a considerable amount of coarse structures are finally contained. As the average fiber diameter, the number average of 50 fibers is calculated, but the presence of nanofibers that cause the aggregation of lumps and the presence of unmilled portions are not evaluated. As a confirmation of the dispersibility of the cellulose fibers in the resin, the presence or absence of coarse structures with a maximum diameter of 200 μm or more in a dry state is confirmed, but the presence or absence of coarse structures smaller than that is not evaluated.

[0009] In the following Patent Document 3, a cellulose raw material is preliminarily treated with an enzyme to decompose the amorphous region and then to refine the fiber, thereby improving the homogeneity and dispersibility of the fiber and obtaining cellulose microfibers. The fiber diameter, fiber length, and fibrillation rate are adjusted by the number of treatments in a refiner, but even with this treatment method, it is impossible to avoid either or both of nanofibrillation and the residue of an un-crushed portion, and a considerable amount of coarse structures are ultimately contained.

[0010] As a method for solving this problem, methods of adding surfactants, drying after solvent replacement to remove water, and chemically modifying cellulose have been reported. In Patent Document 4, as in Patent Document 3, the cellulose raw material is pre-enzymatically treated, and the amorphous region is decomposed and then micronized, thereby obtaining cellulose microfibers with a coefficient of variation of fiber diameter distribution of less than 1.1. The maximum fiber diameter of CNF-B, which has been micronized to obtain microfibers, is 1.271 μm. The 100 fibers observed do not contain aggregates or unbroken parts, but the minimum fiber diameter is 0.022 μm, and a considerable amount of nanofiberized parts have been added. If such microfibers are not added with stabilizers or surfactants, aggregates caused by the aggregation of nanofibers will be generated during storage, and aggregates caused by the entanglement of nanofibers will be generated during stirring, and ultimately a considerable amount of coarse structures will be included.

[0011] In the following patent document 5, cationic surfactant is added to cellulose nanofiber, water is removed in the presence of polyol, hydrophobization is performed with silane coupling agent, and shear force is applied to the rubber component, thereby obtaining a composite material without a coarse structure of more than 1 μm, although nanofiber is used. By using such a special method, the effect as a filler is finally exerted, but surfactants and silane coupling agents are not derived from nature, and then the biodegradability of cellulose is hindered due to their use. Furthermore, it is not a general technology for purposes other than the composite with rubber, and the cost becomes very high.

[0012] As a method for obtaining cellulose microfibers without mechanical treatment or chemical treatment, a method of dissolving cellulose in a solvent for wet spinning and electrostatic spinning has been reported. In the following patent document 6, cellulose is dissolved in a copper ammonia solution and subjected to tension spinning to obtain cellulose microfibers. If this method is used, nanofibers and un-crushed parts will not remain. On the other hand, if the monofilaments are in contact with each other before sufficient desolventization in the spinning funnel, agglomerated fibers formed by the fibers being firmly bonded to each other will be produced. Furthermore, before decopperization using sulfuric acid is performed, desolventization is insufficient, so strong hydrogen bonds are formed between the fibers during decopperization, resulting in agglomerated fibers formed by the fibers being firmly bonded to each other. These agglomerated fibers are also a kind of coarse structure, which can damage the original performance of the microfibers depending on the purpose. In addition, in order to be used for spinning, it is necessary to give the monofilaments a certain degree of self-adhesiveness, and the decopperization of the solvent is refined in a sulfuric acid bath in a rectified state. In this method, the structure is fixed in a state where the tension generated during spinning is not relaxed, so the orientation of the cellulose molecular chains of the obtained fibers is excessive and easy to fibrillate. When easily fibrillated fibers are used as fillers, nanofibers are generated during kneading, and aggregates are formed due to aggregation.

[0013] In the following Patent Document 8, the concentration of cellulose dissolved in a copper ammonia solution is reduced, tension spinning is performed, and the fibers are layered on a web to obtain a nonwoven fabric composed of cellulose microfibers. In this method, before the solvent is fully removed in the funnel, the monofilaments come into contact with each other, and strong hydrogen bonds are formed between the fibers during copper removal to produce agglomerated fibers.

[0014] In the following patent document 7, cellulose is dissolved in a cuprammonium solution and subjected to electrospinning to obtain uniform cellulose microfibers with a fiber diameter CV value of 11 to 30% and a small amount of granular parts with a diameter of 3.0 μm or more. If this method is used, there will be no residue of uncrushed parts, almost no orientation of cellulose, and it is not easy to fibrillate, so even if it is used as a filler, it is not easy to produce nanofibers during kneading. However, it is difficult to fine-tune the coagulation speed in electrospinning, and sometimes it reaches the collector before sufficient desolvation is performed, resulting in agglomerated fibers in which the fibers are firmly bonded to each other. In addition, the granular part in the sheet is 500 pieces / mm 2 The following, when converted to a weight unit, shows that there is a considerable amount of granular part. Furthermore, the fibers obtained by electrospinning have problems such as low orientation of cellulose, limited applications, strong aggregation during drying due to low crystallinity, and low productivity.

[0015] Prior art literature

[0016] Patent Literature

[0017] Patent Document 1: Japanese Patent Application Publication No. 2020-55951

[0018] Patent Document 2: Japanese Patent Application Publication No. 2020-125417

[0019] Patent Document 3: Japanese Patent No. 6799565

[0020] Patent Document 4: Japanese Patent No. 6845510

[0021] Patent Document 5: Japanese Patent Application Publication No. 2021-14512

[0022] Patent Document 6: Japanese Patent No. 5584445

[0023] Patent Document 7: Japanese Patent No. 4871196

[0024] Patent Document 8: Japanese Patent No. 7101879 Summary of the invention

[0025] Problem that the invention aims to solve

[0026] In view of the above-mentioned state of the art, an object of the present invention is to provide cellulose microfibers (fibrous cellulose) having a uniform fiber diameter distribution with a low ratio of both cellulose nanofibers and macroscopic structures, which can be widely used in various applications.

[0027] Solutions for solving problems

[0028] The inventors of the present invention have conducted in-depth research and repeated experiments to solve the above-mentioned problems, and found that the cause of the generation of coarse structures is the aggregation of nanofibrillated cellulose, the residue of uncrushed parts of raw cellulose, and the strong adhesion of fibers. Unexpectedly, it was found that by controlling these to below a certain amount, cellulose microfibers (fibrous cellulose aggregates) with uniform fiber diameters and few coarse structures can be obtained without adding chemical substances or modifying cellulose, thereby completing the present invention.

[0029] That is, the present invention is as follows.

[0030] [1] A cellulose fiber, wherein the average fiber diameter in a dry state observed by electron microscopy is greater than or equal to 0.3 μm and less than or equal to 3.0 μm, the proportion of fibers having a fiber diameter less than 0.1 μm is less than 5%, and the proportion of coarse structures is less than 3.0%, wherein the proportion of coarse structures is determined by the proportion of the number of fibers having a wet fiber diameter of greater than 20 μm as measured by optical automatic analysis.

[0031] [2] The cellulose fibers according to [1] above, wherein the wet average fiber diameter is 1.0 μm or more and less than 10.0 μm.

[0032] [3] The cellulose fiber according to [1] or [2] above, wherein the wet average fiber length is 3000 μm or less.

[0033] [4] The cellulose fiber according to any one of [1] to [3] above, wherein the coefficient of variation of the fiber diameter is 1.00 or less.

[0034] [5] The cellulose fiber according to any one of [1] to [4] above, wherein the aggregation constant of the fiber diameter is 5.0 or less.

[0035] [6] The cellulose fibers according to any one of [1] to [5] above, wherein the crystal structure of the cellulose constituting the cellulose fibers is type II.

[0036] [7] The cellulose fiber according to any one of [1] to [6] above, wherein the crystallinity of the cellulose constituting the fiber is 30% or more and 90% or less.

[0037] [8] A composition comprising the cellulose fiber according to any one of [1] to [7] above.

[0038] [9] A porous body formed from the cellulose fiber according to any one of [1] to [7] above.

[0039] Effects of the Invention

[0040] The cellulose fibers of the present invention are uniform cellulose microfibrils (fibrous cellulose aggregates) with few coarse structures without the addition of chemical substances or modification of cellulose, and can therefore be used in a variety of applications such as fillers for reinforcing resins and rubbers, and base materials for porous bodies such as filters. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the cellulose fibers obtained in Example 1.

[0042] Figure 2 This is a SEM image of the cellulose fibers obtained in Comparative Example 1.

[0043] Figure 3 This is a SEM image of the cellulose fibers obtained in Comparative Example 7.

[0044] Figure 4 is a SEM image of the surface of the porous sheet prepared from the cellulose fibers of Example 1.

[0045] Figure 5 is a SEM image of the surface of the porous sheet prepared from the cellulose fibers of Comparative Example 7.

[0046] Figure 6 This is a SEM-EDX image of a tensile fracture surface of a cellulose fiber-rubber composite body in which the cellulose fiber of Example 1 is composited.

[0047] Figure 7 This is a SEM-EDX image of a tensile fracture surface of a cellulose fiber-rubber composite body in which the cellulose fiber of Comparative Example 6 is composited.

[0048] Figure 8 This is a SEM image of the cellulose fibers obtained in Comparative Example 4.

[0049] Fig. 9 This is a SEM image of the cellulose fibers obtained in Comparative Example 8.

[0050] Fig.10 is a SEM image of the surface of the porous sheet prepared from the cellulose fibers of Comparative Example 4.

[0051] Fig.11 This is a SEM-EDX image of the tensile fracture surface of the cellulose fiber-rubber composite body compounded with the cellulose fiber of Example 1-3. DETAILED DESCRIPTION

[0052] Hereinafter, embodiments of the present invention will be described in detail.

[0053] One embodiment of the present invention is a cellulose fiber, wherein the average fiber diameter in a dry state observed by electron microscopy is greater than or equal to 0.3 μm and less than or equal to 3.0 μm, the proportion of fibers with a fiber diameter less than 0.1 μm is less than 5%, and the proportion of coarse structures is less than 3.0%, wherein the proportion of coarse structures is measured by the proportion of the number of fibers having a wet fiber diameter of greater than 20 μm as measured by optical automatic analysis.

[0054] [Cellulose fiber]

[0055] In this specification, the term "cellulose fiber" refers to a structure (aggregate) comprising fibrous cellulose, and its manufacturing method is not particularly limited, and can include a method of utilizing physical force to refine the cellulose raw material, a method of utilizing chemical force to refine the cellulose raw material, a method of dissolving in a solvent and forming it into a fibrous shape, etc. In addition, they can also be combined. In order to further reduce the cellulose nanofibers that become the cause of the coarse structure, the unbroken part of the raw material, preferably the method of dissolving the cellulose raw material in a solvent and forming it into a fibrous shape. By dissolving in a solvent, it is also possible to utilize filtration and centrifugation to remove tiny foreign matter.

[0056] In this specification, the term "fiber diameter" of cellulose fibers refers to the value measured in a dry state of cellulose, and the "average fiber diameter" is an index mean. There are many methods for measuring in a dry state, and it can be selected according to the fiber diameter. As described later, the measurement is performed using an electron microscope in the examples.

[0057] The cellulose fibers of the present embodiment are evaluated not only in a dry state but also in a wet state. In the evaluation in a dry state using an electron microscope or the like, it is difficult to distinguish between the fibers that were originally aggregated and the fibers that aggregated when dry. In addition, the results also vary depending on the location of the measurement. Furthermore, there is a limit to the number of roots that can be measured in a dry state, and there is a certain degree of accuracy when only the average value is evaluated, but it is difficult to evaluate the distribution. The result of the evaluation in a wet state is to express the fiber diameter as "Wet fiber diameter" and the average fiber diameter as "Wet average fiber diameter", which are distinguished from the result of the evaluation in a dry state. It should be noted that since the cellulose fibers swell in water, the "Wet fiber diameter" is larger than the "fiber diameter".

[0058] There are various methods for evaluating in a wet state, and from the perspective of being able to distinguish between fiber diameter and fiber length, preferably a microscope, a microscope, or an optical automatic analysis method can be selected according to the fiber diameter. As described later, an optical automatic analysis method is used for measurement in the examples.

[0059] The "average fiber diameter" of the "fiber diameter" of the cellulose fiber of the present embodiment is 0.3 μm or more and 3.0 μm or less. When the average fiber diameter is 0.3 μm or more, it is possible to suppress the aggregation of fibers caused by intermolecular forces during storage, the aggregation caused by entanglement during stirring, the aggregation caused by hydrogen bonds during drying, etc. The average fiber diameter is preferably 0.4 μm or more, more preferably 0.5 μm or more, and further preferably 0.7 μm or more. On the other hand, if the average fiber diameter is 3.0 μm or less, the number of fibers per unit weight increases, so there are effects such as an increase in the addition effect as a filler and an increase in the specific surface area when a porous body is made. The average fiber diameter is preferably 2.5 μm or less, more preferably 2.0 μm or less, further preferably 1.5 μm or less, and most preferably 1.0 μm or less.

[0060] The "ratio of fibers with a fiber diameter of less than 0.1 μm" of the cellulose fibers of this embodiment is 5% or less. By making the amount of nanofibers with a fiber diameter of less than 0.1 μm less than 5%, it is possible to suppress not only the aggregation of fibers during storage, aggregation due to entanglement during stirring, and aggregation due to hydrogen bonding during drying, but also the deterioration of operability due to increased viscosity. The "ratio of fibers with a fiber diameter of less than 0.1 μm" is preferably 4% or less, more preferably 3% or less, further preferably 2% or less, particularly preferably 1% or less, and most preferably 0%.

[0061] In the present specification, the term "cellulose nanofiber" refers to cellulose fibers having a fiber diameter of less than 0.1 μm. In addition, the term "cellulose microfiber" refers to cellulose fibers having a fiber diameter of 0.1 μm or more and less than 9.7 μm.

[0062] In this specification, the term "coarse structure" refers to a structure whose maximum width of the short side orthogonal to the long side is 20.0 μm or more in a wet state as described later. Coarse structures include not only aggregates of structures smaller than 20.0 μm such as aggregates caused by the aggregation of nanofibers, entanglement of fibers, agglomerated fibers formed by fibers firmly bonded to each other, residues of the uncrushed part of the cellulose raw material, and cellulose blocks such as coarse fibers that were originally larger than 20.0 μm, but also foreign matter contained in the cellulose raw material. The reason for using the measurement results in a wet state is that the evaluation in a dry state cannot distinguish between the original aggregation and the aggregation when dry. Furthermore, it is also because the measurement in a wet state can easily increase the number of measurements and enable accurate distribution evaluation. Although it also depends on the preparation method and crystal structure of the cellulose fiber, by reducing the structures that are more than 20.0 μm in a wet state, the structures that are about 10.0 μm or more in a dry state can be reduced.

[0063] The "ratio of coarse structures" described later in the cellulose fiber of the present embodiment is 3.0% or less. If the coarse structures are 3.0% or less, it is possible to expect effects such as reduction of defects when used as a filler, reduction of defects when used as a base material for a porous body, and improvement of functions due to an increase in the number of fibers. The "ratio of coarse structures" is preferably 2.0% or less, more preferably 1.0% or less, and further preferably 0.5% or less. The "ratio of coarse structures" is preferably smaller, but from the viewpoint of production efficiency, it is preferably 0.1% or more.

[0064] The "coefficient of variation of fiber diameter" of the cellulose fiber of the present embodiment is preferably 1.00 or less. Fibers with uniform fiber diameters whose coefficient of variation of fiber diameter is 1.00 or less have less functional degradation due to the cutting of thin fibers and less defects due to coarse fibers, and are easy to exert the desired performance in various applications. In addition, the fiber length can be made uniform when short-fiberized due to physical impact. The "coefficient of variation of fiber diameter" is preferably 0.70 or less, more preferably 0.50 or less, further preferably 0.40 or less, particularly preferably 0.30 or less, and most preferably 0.20 or less. The "coefficient of variation of fiber diameter" is preferably smaller, but from the viewpoint of production efficiency, it is preferably 0.05 or more.

[0065] The "Wet average fiber diameter" described later of the cellulose fiber of the present embodiment is preferably not less than 1.0 μm and not more than 10.0 μm. By making the Wet average fiber diameter not less than 1.0 μm, it is possible to suppress the aggregation of fibers during storage, aggregation due to entanglement during stirring, aggregation due to hydrogen bonds during drying, etc. The "Wet average fiber diameter" is preferably not less than 1.3 μm, and particularly preferably not less than 1.7 μm. On the other hand, when the "Wet average fiber diameter" is not more than 10.0 μm, the number of fibers per unit weight increases, thereby having the effects of improving the addition effect as a filler and increasing the specific surface area when made into a porous body. The "Wet average fiber diameter" is preferably not more than 8.3 μm, more preferably not more than 6.7 μm, further preferably not more than 5.0 μm, and particularly preferably not more than 3.3 μm.

[0066] In this specification, the term "aggregation constant" is an index showing the degree of aggregation of cellulose fibers, and is defined by the following formula.

[0067] Aggregation constant = (Wet average fiber diameter ÷ average fiber diameter)

[0068] Cellulose fibers with a large number of nanofibers with a fiber diameter of less than 0.1 μm appear to be dispersed in local observations such as SEM, but in fact, part of the fibers are not crushed, or a network structure is formed by hydrogen bonds. The Wet fiber diameter of such cellulose fibers tends to increase. In addition, cellulose fibers with a large number of aggregated fibers formed by fibers firmly bonded to each other, which appear to be independent fibers overlapping in SEM, also tend to have a large Wet fiber diameter.

[0069] The "aggregation constant" of the cellulose fiber diameter of the present embodiment is preferably 5.0 or less. By making the aggregation constant 5.0 or less, it is possible to expect the effects of reducing defects when used as a filler, reducing defects when used as a base material for a porous body, and improving functions brought about by increasing the number of fibers. The "aggregation constant" is more preferably 4.0 or less, further preferably 3.0 or less, and particularly preferably 2.5 or less. The "aggregation constant" is preferably smaller, but from the viewpoint of production efficiency, it is preferably 1.0 or more, and more preferably 1.5 or more.

[0070] The "coefficient of variation of wet fiber diameter" of the cellulose fiber of the present embodiment is preferably 1.00 or less. Fibers with uniform fiber diameters having a coefficient of variation of wet fiber diameter of 1.00 or less have less functional degradation due to the cutting of thin fibers and less defects due to coarse fibers, and are more likely to exhibit desired performance in various applications. In addition, the fiber length can be made uniform when short-fibered due to physical impact. The "coefficient of variation of wet fiber diameter" is preferably 0.90 or less, more preferably 0.80 or less, further preferably 0.70 or less, particularly preferably 0.60 or less, and most preferably 0.50 or less. The "coefficient of variation of wet fiber diameter" is preferably smaller, but from the viewpoint of production efficiency, it is preferably 0.20 or more.

[0071] The "crystal structure (crystal form)" of the cellulose fiber of the present embodiment is not particularly limited, and various celluloses of type I, type II, type III, and type IV can be used. In addition, the "crystallinity" of the cellulose fiber of the present invention is also not particularly limited, and cellulose fibers of any crystallinity can be used. When adjusting the fiber length in a wet state, a type II crystal structure that can cut the fiber with a weak force and easily become uniform is preferred.

[0072] The "crystallinity" of the cellulose fiber of this embodiment is preferably 30% or more and 90% or less. If the crystallinity is above a certain level, aggregation during drying can be reduced, and the strength of the cellulose fiber also increases. Therefore, the crystallinity is preferably 30% or more, more preferably 40% or more, and particularly preferably 50% or more. On the other hand, if the crystallinity is below a certain level, the dispersibility when used as a filler is improved, or when used as a substrate for a porous body, the fibers are bonded to each other at the intersection and the strength of the substrate increases. Therefore, the crystallinity is preferably 90% or less, more preferably 80% or less, and further preferably 70% or less. It should be noted that several methods for calculating the crystallinity of cellulose have been proposed. In this embodiment, it refers to the crystallinity calculated by the Segal method.

[0073] The cross-sectional shape of the cellulose fiber of the present embodiment is not particularly limited, and fibers of various cross-sectional shapes such as circular, irregular, and amorphous can be used, and the surface can be fibrillated. From the perspective of the reinforcing effect when used as a filler and the repair effect when the porous body is used as a filter, a circular cross-section is preferred. In addition, when using cellulose fiber as a filler, in order to suppress the shedding of the fiber, the surface is preferably fibrillated.

[0074] The "fiber length" and "wet fiber length" of the cellulose fiber of the present embodiment can be adjusted to any length. When using a method in which cellulose is dissolved in a solvent and formed into a fibrous state, it can be obtained in the form of very long fibers, or in the form of short fibers by cutting the obtained long fibers. When used in the form of short fibers, the fiber length and wet fiber length can be selected according to the application. It should be noted that the "average fiber length" and "wet average fiber length" in the present invention represent the length-weighted average fiber length.

[0075] When the cellulose fiber of the present embodiment is used for filler purposes, the "Wet average fiber length" is preferably 20 μm or more and 3000 μm or less. If the Wet average fiber length is above a certain value, the fiber is not easy to fall off even if stress is applied, and the reinforcing effect becomes higher, so it is more preferably 30 μm or more, further preferably 40 μm or more, and particularly preferably 50 μm or more. On the other hand, if the Wet average fiber length is below a certain value, the number of fibers increases, thereby improving the reinforcing effect, and it is also possible to suppress the generation of coarse structures caused by fiber entanglement during kneading, so it is more preferably 1000 μm or less, further preferably 800 μm or less, further preferably 600 μm or less, and particularly preferably 400 μm or less.

[0076] When the cellulose fiber of the present embodiment is used as a substrate for a porous body, the "Wet average fiber length" is preferably 50 μm or more and 3000 μm or less. If the Wet average fiber length is above a certain value, even if drying shrinkage occurs during drying, the fibers can be interwoven to maintain a porous structure, so it is more preferably 100 μm or more, and more preferably 200 μm or more. On the other hand, if the Wet average fiber length is below a certain value, the entanglement of the fibers can be suppressed, so it is more preferably 2000 μm or less, more preferably 1000 μm or less, and particularly preferably 800 μm or less.

[0077] The "coefficient of variation of wet fiber length" of the cellulose fiber of the present embodiment is preferably 1.00 or less. Fibers with uniform fiber length whose coefficient of variation of wet fiber length is 1.00 or less can suppress the generation of aggregates due to fiber entanglement. As a result, the desired performance can be exerted when used for various purposes. The "coefficient of variation of wet fiber length" is more preferably 0.90 or less, further preferably 0.80 or less, particularly preferably 0.70 or less, and most preferably 0.60 or less. The "coefficient of variation of wet fiber length" is preferably smaller, but from the viewpoint of production efficiency, it is preferably 0.05 or more.

[0078] The cellulose fiber of the present embodiment can also make both the fiber diameter and the fiber length uniform, and by making both uniform, the effect of using the fiber in various applications can be effectively exerted. Both the "coefficient of variation of wet fiber diameter" and the "coefficient of variation of wet fiber length" are preferably 1.00 or less. Preferably, both are 0.90 or less, more preferably, both are 0.80 or less, further preferably, both are 0.70 or less, particularly preferably, both are 0.60 or less, and particularly preferably, both are 0.50 or less. Both the "coefficient of variation of wet fiber diameter" and the "coefficient of variation of wet fiber length" are preferably smaller, but from the viewpoint of production efficiency, they are preferably 0.05 or more.

[0079] The cellulose fiber of this embodiment can also react a part of its hydroxyl groups to make a cellulose derivative, and any substituent can be introduced according to the required function. In order to maintain the biodegradability of cellulose, it is preferably a substituent that does not cause hydrophobization of cellulose, and the degree of substitution is preferably 0.30 or less, more preferably 0.20 or less, particularly preferably 0.10 or less, and particularly preferably 0.05 or less. In order to maintain the biodegradation rate of cellulose and make the environmental impact after decomposition also good, it is preferred to use cellulose directly without derivatization.

[0080] The cellulose fiber of the present embodiment can be used as required in the form of an aqueous solution formed by being dispersed in water, in addition, a surfactant, an inorganic salt, a water-soluble polymer, etc. can be added for use, and other liquids compatible with water can be added as required, or it can be dispersed in a non-aqueous solvent. Of course, it can also be mixed with solid components such as other fibers, particles, fillers. When adding a surfactant, from the perspective of making the biodegradability of cellulose, the environmental impact after decomposition good, it is preferably anionic, amphoteric, nonionic, and its usage amount is preferably below 10 weight %. More preferably below 3 weight %, further preferably below 1 weight %, particularly preferably below 0.1 weight %, most preferably do not add a surfactant.

[0081] The cellulose fiber of this embodiment can be used in a dry solid state as needed. In order to suppress aggregation during drying, freeze drying, solvent replacement drying, solvent replacement freeze drying, supercritical drying, etc. can be performed. Surfactants, inorganic salts, oils, etc. can be added, and cellulose derivatives can also be made from the hydroxyl groups of cellulose.

[0082] [Method for producing cellulose fibers]

[0083] An example of the method for producing the cellulose fiber of the present invention is described below, but the present embodiment is not limited to this production method.

[0084] The cellulose raw material is not particularly limited, and various raw materials can be selected. For example, wood pulp, non-wood pulp, cotton, cotton linter and other cotton pulp, cellulose from sea squirt, seaweed and the like, recovered pulp, recycled cellulose and the like can be listed. In addition, a plurality of them can also be used in combination. Among them, cotton and cotton linter pulp are preferred from the aspect of high purity, and cotton linter is particularly preferred.

[0085] The solvent for dissolving cellulose is not particularly limited, and various known solvents can be selected. Examples thereof include copper ammonia solution, viscose solution, acid or alkali of a specific concentration, aqueous solutions of inorganic salts such as zinc chloride, N-methylmorpholine N-oxide, and various ionic liquids. Among them, copper ammonia is preferably used as the solvent from the viewpoints of being able to adjust the coagulation speed, easily thinning the fiber diameter, and being able to adjust fibrillation.

[0086] The method of dissolving cellulose in a solvent and forming it into a fiber shape is not particularly limited, and various spinning methods can be used. For example, the following methods can be cited: down-flow tension spinning in which a solution is extruded from a spinning nozzle having many holes, and the solution is coagulated by flowing in a funnel together with a coagulation liquid for desolvation; air-gap spinning in which the solution is ejected once in the air and then coagulated with a coagulation liquid; dry spinning in which the solution is stretched and desolvated in the air; melt-blown spinning in which the solution is stretched and coagulated with a high-speed air flow; electrostatic spinning in which the solution is charged and thinned and accumulated by electrical repulsion, etc. Among them, down-flow tension spinning, air-gap spinning, and melt-blown spinning in which the orientation of cellulose can be controlled are preferred, and down-flow tension spinning in which the fiber diameter can be made uniform, the fiber is not easily broken even if the fiber diameter becomes thinner, and strong adhesion between the fibers can be suppressed is particularly preferred.

[0087] Hereinafter, a case where cellulose is dissolved in a cuprammonia solution and downward tension spinning is performed will be described as an example.

[0088] The concentration of cellulose dissolved in the copper ammonia solution can be arbitrarily selected. Although it also depends on the degree of polymerization of the dissolved cellulose, it is preferably 1 to 20% by weight. In addition, it is preferred to filter, centrifuge, etc. after dissolving the cellulose to remove foreign matter and undissolved matter. If the concentration is above a certain level, the viscosity of the stock solution becomes high, and the broken ends in the funnel are suppressed, so that the effect of uniform stretching can be obtained, and it is not easy to contact with other fibers before sufficient desolvation, and the effect of the monofilaments being firmly bonded to each other can be obtained, and the fiber diameter of the obtained fiber becomes uniform. In addition, the monofilament strength of the obtained fiber is also improved.

[0089] The concentration of cellulose dissolved in the copper ammonia solution is more preferably 2% by weight or more, more preferably 3% by weight or more, and particularly preferably 4% by weight or more. In addition, if the concentration is below a certain value, it is easy to stretch, so that the fiber diameter can be thinned, and foreign matter can be easily removed by filtering and centrifuging the stock solution. The concentration of cellulose dissolved in the copper ammonia solution is more preferably 9% by weight or less, more preferably 8% by weight or less, and particularly preferably 7% by weight or less. In addition, the ammonia concentration is preferably 10% by weight or less, more preferably 9% by weight or less, and further preferably 8% by weight or less. If within this range, uneven coagulation is not easy to occur, and the fibers can be suppressed from being firmly combined with each other.

[0090] The nozzle for ejecting the dissolving solution can use a nozzle of any shape. As the number of holes, it is preferably 10 to 2000. If the number of holes is 2000 or less, the internal and external differences of coagulation can be produced within a certain range, and the uniform fiber diameter becomes uniform. In addition, by making the flow rate of the coagulating solution below a certain level, the flow in the funnel can be rectified, and the fibers can be prevented from contacting each other before sufficient desolvation. The number of holes is more preferably 1500 or less, further preferably 1000 or less, and particularly preferably 500 or less. From the perspective of productivity, the number of holes is more preferably 50 or more. In addition, as the hole diameter, it is preferably 0.05 to 0.50 mm. If the hole diameter is 0.05 mm or more, the productivity is high, sufficient stretching can be given, and the strength of the cellulose fiber can be improved. In addition, the ejection speed of the dissolving solution can be made below a certain level, the dissolving solution can be prevented from shaking in the coagulating solution, and the fibers can be prevented from contacting each other before sufficient desolvation. The hole diameter is more preferably 0.08 mm or more, and more preferably 0.10 mm or more. On the other hand, if the hole diameter is less than 0.50, the solution ejected from the spinneret can take a certain distance, which can inhibit the fibers from contacting each other before sufficient desolvation. In addition, excessive stretching can be inhibited, and the cellulose fibers are not easily fibrillated, which can inhibit the generation of fine fibers during short fiberization and mixing due to physical impact. The hole diameter is more preferably less than 0.40 mm, and more preferably less than 0.30 mm. Furthermore, the distance between holes from the end to the end of adjacent holes is preferably 0.60 to 2.00 mm. If the distance between holes is more than 0.60 mm, even if the dissolved solution is slightly shaken in the coagulation solution, the fibers can be inhibited from contacting each other. In addition, the spinneret is provided with holes in multiple rows on concentric circles, so that the solution ejected from the holes in the outermost layer contacts the fresh coagulation solution, but the solution ejected from the holes in the inner layer may coagulate unevenly. If the distance between the holes is 0.60 mm or more, the coagulation solution easily diffuses to the inner layer, and the coagulation unevenness of the solution ejected from the holes in the inner layer can be suppressed, and as a result, the fibers can be suppressed from contacting each other before sufficient desolvation is performed. The distance between the holes is more preferably 0.80 mm or more, and more preferably 1.0 mm or more.

[0091] The coagulation liquid may be any liquid capable of deamination, but it is preferred to use water having a controlled temperature from the viewpoint of economy and safety. In order to obtain cellulose fibers having a thin average fiber diameter, it is necessary to lower the spinning water temperature for stretching, but sometimes the coagulation of the dissolved liquid ejected from the holes of the inner layer becomes insufficient. When decoppering is performed in this state, a strong hydrogen bond is formed between the fibers. Therefore, it is preferred to first perform stretching and coagulation at a low spinning water temperature, and then complete the coagulation of the dissolved liquid ejected from the holes of the inner layer at a high spinning water temperature.

[0092] After deamination is performed in the funnel and fibers are formed, the method for decoppering can be arbitrarily selected. For example, the method of adding acid into the funnel, the method of spraying into the acid bath after coming out of the funnel, the method of diverting the original silk (Japanese: blue silk) after coming out of the funnel to immerse it in the acid bath, the method of dripping acid into the original silk, the method of spraying acid after connecting to a mesh, and the method of adding acid intermittently after connecting to a tank. By decoppering under a low tension applied to the silk, the cellulose fiber is not easy to fibrillate. In addition, it is easy to liquid-renew the acid between the fibers, improve the decoppering efficiency, and obtain cellulose fibers with less residual copper and residual sulfuric acid. In the method for manufacturing cellulose fibers of the present embodiment, a method of spraying sulfuric acid after the tension is relaxed by receiving it with a mesh after coming out of the funnel, and a method of suppressing the increase of tension by spraying sulfuric acid on the original silk that has changed direction after coming out of the funnel are used. On the other hand, when deamination is performed by a method in which cellulose is not stretched sufficiently, such as electrospinning, the strength of the obtained cellulose fibers can be increased by applying a certain degree of tension to perform copper removal.

[0093] The method for removing the acid after decoppering with an acid can be arbitrarily selected. Since the fibers are thin when the acid is removed, it is difficult to renew the liquid between the fibers, so a method that easily renews the liquid is preferred. In the method for producing cellulose fibers of this embodiment, washing with warm water is repeated to remove sulfuric acid.

[0094] The cellulose fibers preferably have low residual copper and residual sulfuric acid contents. If these contents are high, there are effects such as aggregation of the fibers during drying, reduction in strength during storage, and reduction in biodegradability.

[0095] When the cellulose fibers are dried, the method can be arbitrarily selected. For example, heating drying, reduced pressure drying, air drying, freeze drying, solvent replacement drying, supercritical drying or a combination thereof can be performed. In order to suppress aggregation during drying, an oil agent can also be added.

[0096] The fiber diameter of the cellulose fibers can be arbitrarily adjusted by the concentration of dissolved cellulose, the diameter of the nozzle for ejecting the dissolving solution, the funnel shape, the stretching ratio based on the combination of the temperature, composition and flow rate of the coagulation solution, and the like.

[0097] As a method for adjusting the fiber length of cellulose fibers, various methods can be used depending on the desired fiber length, and examples thereof include a method of cutting the fibers with a blade and a method of applying a physical impact to the fibers to shorten them.

[0098] Examples of methods for cutting cellulose fibers using a cutting tool include a rotary cutter, a guillotine cutter, a shredder, and the like. In addition, the cellulose fibers may be cut in a dry state, in a wet state, or in a state suspended in water or an organic solvent. Chemical treatment or heat treatment may also be performed in advance. The method of cutting with a cutting tool makes it easy to keep the fiber length constant, but there is a limit to the fiber length that can be shortened.

[0099] As examples of methods for short-fibering using physical impact, mixers, homogenizers, ball mills, beaters, disc mills, grinders, high-pressure homogenizers, etc. can be cited. The method of short-fibering using physical impact can shorten the fiber length, but the fiber length of the obtained fiber is prone to a certain distribution. In particular, when natural cellulose is fined using physical force, due to the distribution of fiber diameter, the thinner and easier to cut part and the thicker and more difficult to cut part are mixed together, so it is easy to produce a distribution of fiber length. On the other hand, the fiber diameter of the cellulose of the present application is uniform, so it is possible to suppress the expansion of the fiber length distribution to a certain extent. In addition, when short-fibering using physical impact, it is not suddenly short-fibered from long fibers, but physical impact is applied after cutting into a certain length using a blade in advance, thereby further suppressing the expansion of the fiber length distribution. In addition, by filtering and grading using a filter after short-fibering, it is also possible to remove fibers whose fiber length becomes too short, or to remove residual fibers whose fiber length is still long.

[0100] When physical impact is used to short-fiberize, if the impact is too strong, the fiber will be fibrillated and cut, and the distribution of fiber diameter will become wider. In other words, the purpose of applying physical impact to the fiber is to shorten the fiber length and peel off the attached fibers formed by the fibers being bonded to each other with a weak force, rather than to reduce the fiber diameter. When it is desired to make the fiber length very short, it is preferably combined with a method of suppressing the orientation of cellulose, reducing the degree of polymerization of cellulose, etc. in order to suppress the fibrillation of the fiber as needed.

[0101] [Application of cellulose fiber]

[0102] The cellulose fiber of this embodiment can be used as a filler added to resin or rubber, a porous body that can be used in filters, adsorbents, sound absorbing materials, heat insulating materials, etc., a coating agent, a base material for artificial leather, an anti-settling agent for liquid products, etc. Cellulose fibers with few nanofibers and coarse structures can be obtained as a uniformly dispersed and uniform porous body as a filler without adding a surfactant or hydrophobizing the cellulose.

[0103] Hereinafter, an example of using the cellulose fiber of the present embodiment as a porous body is described. Of course, the present invention is not limited thereto. When the cellulose fiber of the present embodiment is used to make a porous body, the cellulose fiber can be used alone, or mixed with other cellulose fibers or other raw material fibers, or stacked with other porous bodies. Hereinafter, an example of forming a porous body by cellulose fiber alone is described. It should be noted that when the cellulose fiber is used to form a porous body, a surfactant, a pore size retaining agent, or hydrophobization of the cellulose is not performed, and the sheeting is implemented by the simplest heating and drying to evaluate the influence of the shape of the cellulose fiber on the formation of the porous body.

[0104] The method for forming a porous body from cellulose fibers is not particularly limited, and various known methods can be used. Examples thereof include air-laid method, spunlace method, needle punching method, papermaking method, chemical bonding method, freeze drying method, etc. From the perspective of obtaining a homogeneous porous body by a simple method, papermaking method is preferred.

[0105] The liquid for suspending the cellulose fibers during papermaking is preferably a liquid in which the cellulose does not aggregate. From the viewpoint of dispersibility, water is preferred, but from the viewpoint of drying efficiency and suppression of aggregation during drying, alcohols such as methanol, ethanol, isopropanol, and tert-butyl alcohol, ketones such as acetone and methyl ethyl ketone, and ethers such as diethyl ether are also preferred. Of course, these liquids may be mixed in any ratio for use.

[0106] The method of drying after papermaking is not particularly limited. When the crystal structure of the cellulose fibers is type II, the drying is preferably carried out at a temperature of 200°C or lower, more preferably 190°C or lower, and even more preferably 180°C or lower.

[0107] In the following examples, the obtained cellulose fiber sheet was used to evaluate the performance as a porous body.

[0108] Hereinafter, an example of using the cellulose fiber of the present embodiment as a filler is described. Of course, the present embodiment is not limited thereto. When the cellulose fiber of the present embodiment is used as a filler, the object of its mixing is not particularly limited, and it can be used as a filler of various resins and rubbers. Hereinafter, a masterbatch is prepared by mixing natural rubber latex with cellulose fiber, and after mixing, vulcanization and hot pressing are performed to obtain an example of a composite of cellulose fiber and rubber. It should be noted that in the following embodiments, when cellulose fiber and rubber are composited, solvent replacement, freeze drying, addition of surfactants, polyols, hydrophobization of cellulose, addition of other fillers, etc. of cellulose fiber are not performed, and composited by a simple method is utilized to evaluate the influence of the shape of cellulose fiber on composited.

[0109] The cellulose fiber and natural rubber latex can be mixed by adding the cellulose fiber in a dry state or in a slurry state suspended in water or an organic solvent. In order to disperse the cellulose fiber more evenly, it is preferably added in a slurry state. The cellulose fiber and natural rubber latex are preferably mixed using a rotary-revolution type mixer. The obtained aqueous solution in which natural rubber latex and cellulose fiber are suspended is dried to prepare a masterbatch.

[0110] The cellulose concentration in the masterbatch is preferably 1.0 to 20.0% by weight or more. Since the dispersibility is high and the presence of water makes it difficult to form a network structure, when the cellulose concentration is low, the cellulose fibers settle during drying and the uniformity of the obtained masterbatch deteriorates. The lower limit of the cellulose concentration in the masterbatch is more preferably 1.5% by weight or more, and further preferably 2.0% by weight or more.

[0111] The method for kneading the obtained masterbatch can use a known method. For example, a Banbury mixer and an open mill can be listed. After the masterbatch is kneaded, stearic acid, zinc oxide, sulfur, and a vulcanization accelerator are added and further kneaded. Carbon black and the like can also be added as needed. Furthermore, thereafter, vulcanization and molding are performed by hot pressing and cooling and pressing to obtain a composite of cellulose fiber and rubber. When the crystal structure of the cellulose fiber is type II, the temperature for performing a series of operations is preferably below 200°C, more preferably below 190°C, and further preferably below 180°C. The obtained composite is punched into a dumbbell shape, and the composite is evaluated.

[0112] The cellulose fiber of the present embodiment has biodegradability that degrades in compost, soil, and ocean. In particular, biodegradation in the ocean is difficult to degrade due to the small number of microorganisms and the difficulty in raising the temperature. Therefore, in order to accelerate the degradation rate in the ocean, the cellulose is preferably not hydrophobically modified. In addition, considering the safety of the degradable product, it is preferred not to add a surfactant or an additive corresponding to various uses.

[0113] Example

[0114] The present invention will be described in detail below by way of examples and comparative examples, but the present invention is not limited to these examples. In addition, all operations not specifically described were performed under an environment of a temperature of 23° C. and a relative humidity of 55% RH.

[0115] First, various measurement methods and the like used in Examples and Comparative Examples are described.

[0116] [Average fiber diameter]

[0117] The solid content concentration of cellulose fiber relative to pure water is adjusted to 0.10-0.01% by weight, and the cellulose fiber is precipitated by centrifugation, and the operation of resuspending with ethanol is performed 3 times, and the solvent is replaced with ethanol. Further, the cellulose fiber is precipitated by centrifugation, and the operation of resuspending with tert-butyl alcohol is performed 3 times, and the solvent is replaced with tert-butyl alcohol. After solvent replacement, freeze drying is performed, and osmium is evaporated to make an observation sample. For this sample, an electron microscope is used to observe it according to the fiber diameter at any magnification of 1000 times, 10000 times, and 30000 times. Specifically, two diagonal lines are drawn in the observation image, and a straight line passing through the intersection of the diagonal lines is drawn arbitrarily, and the width of 25 fibers interlaced with the straight line is visually measured. Change the observation place, enlarge other places, perform the same measurement, observe a total of 4 places, and calculate the average value from the width of a total of 100 fibers as the average fiber diameter.

[0118] However, when the fiber width is measured visually, if two or more fibers are attached and there is no separated portion in the field of view of the image, they are regarded as attached at the stage of sample preparation, and the widths of the respective fibers are measured as different fibers.

[0119] [Coefficient of variation of fiber diameter (CV)]

[0120] The standard deviation of the 100 measured values ​​in the measurement of the average fiber diameter was calculated using the following formula:

[0121] Coefficient of variation of fiber diameter={(standard deviation of fiber diameter)÷(average fiber diameter)}.

[0122] [Ratio of nanofibers]

[0123] The ratio (%) of nanofibers was calculated from the measured value of 100 fibers in the measurement of the average fiber diameter using the following formula:

[0124] The ratio of nanofibers (%)={(the number of fibers having a diameter less than 0.10 μm)÷100}×100.

[0125] [Wet average fiber diameter]

[0126] The wet average fiber diameter was measured by optical automatic analysis using the Fiber Image Analyzer "Valmet FS5" manufactured by VALMET. However, fibers with too fine a fiber diameter cannot be measured due to resolution, so accurate measurement is not possible. Cellulose fibers with an average fiber diameter of 0.3 μm or less measured by an electron microscope are recorded as reference values.

[0127] The solid content concentration of cellulose fibers relative to pure water was automatically adjusted to a range of 0.005 to 0.0005 wt % using "Valmet FS5", and 300 cc of the cellulose fibers were placed in a plastic beaker. After being dispersed in a bath ultrasonic disperser for 1 minute while placed in the beaker, the fibers were placed in Valmet FS5, and various parameters were set as follows for measurement.

[0128] Minimum fiber length[mm]:0

[0129] Maximum fiber length[mm]:7.6

[0130] Minimum fiber width [μm]: 0

[0131] Maximum fiber width[μm]:20

[0132] Fiber width calculation:1.All fibers

[0133] Images per analysis: 2000

[0134] Analysis mode: 1.normal

[0135] Image noise level[%]: 3

[0136] The fiber width (unit: μm) of the obtained measurement result was adopted as the wet average fiber diameter.

[0137] However, when the solid content concentration of cellulose fibers relative to pure water is in the range of 0.005 to 0.0005 weight %, if the wet average fiber diameter cannot be measured by optical automatic analysis, the solid content concentration is increased by 0.005 weight % at a time from 0.005 weight % to 0.010 weight %, 0.015 weight %, 0.020 weight %, and 0.025 weight % to measure the wet average fiber diameter. When the concentration is too high to be measured, automatic adjustment is performed, and a value that remains constant even if the concentration changes is set as the wet average fiber diameter.

[0138] [Coefficient of variation of wet fiber diameter]

[0139] Based on the measurement results of Valmet FS5, the standard deviation of the wet fiber diameter was calculated, and the coefficient of variation of the wet fiber diameter was calculated using the following formula:

[0140] Coefficient of variation of wet fiber diameter = {(standard deviation of wet fiber diameter) ÷ (wet average fiber diameter).

[0141] [Wet average fiber length]

[0142] Based on the measurement results of Valmet FS5, the length-weighted average fiber length Lc (l) (unit: mm) is used to calculate the Wet average fiber length using the following formula:

[0143] Wet average fiber length (μm) = Lc (l) × 1000.

[0144] However, when the solid content concentration of cellulose fibers relative to pure water is in the range of 0.005 to 0.0005 weight %, if the wet average fiber length cannot be measured by optical automatic analysis, the solid content concentration is increased by 0.005 weight % at a time from 0.005 weight % to 0.010 weight %, 0.015 weight %, 0.020 weight %, and 0.025 weight % to measure the wet average fiber length. When the concentration is too high to be measured, automatic adjustment is performed, and a value that remains constant even if the concentration changes is set as the wet average fiber length.

[0145] [Coefficient of variation of wet fiber length]

[0146] Based on the measurement results of Valmet FS5, the standard deviation of the length-weighted average fiber length was calculated, and the coefficient of variation of the Wet fiber length was calculated using the following formula:

[0147] Coefficient of variation of wet fiber length = {(standard deviation of wet fiber length) ÷ (wet average fiber length)}.

[0148] [Proportion of macroscopic structures (%)]

[0149] Based on the measurement results of Valmet FS5, the ratio (%) of coarse structures was calculated using the following formula using the fiber count (unit: fiber):

[0150] Ratio of macroscopic structures (%)={(number of fibers having a wet fiber diameter of 20 μm or more)÷(Fiber count)}×100.

[0151] The number of fibers to be measured is 1,000 or more.

[0152] [Aggregation constant of fiber diameter]

[0153] The aggregation constant of the fiber diameter was calculated using the following formula:

[0154] Aggregation constant for fiber diameter = (Wet average fiber diameter) ÷ (average fiber diameter).

[0155] [Crystallinity]

[0156] The dry cellulose fibers obtained in the measurement of the average fiber diameter were measured using an X-ray diffractometer (RINT2200 manufactured by Rigaku), and the crystallinity (%) was calculated from the obtained strength curve using the following formula proposed by Seagal et al.:

[0157] Crystallinity (%)={(diffraction intensity at 200° plane)−(diffraction intensity at amorphous portion)}÷(diffraction intensity at 200° plane)×100.

[0158] [Preparation of porous body]

[0159] A water suspension having a cellulose fiber concentration of 0.10 wt% relative to pure water was prepared, a cellulose filter paper was placed on a Buchner funnel, and the suspension was filtered while reducing the pressure to 0.01 MPa so that the cellulose content was 40 g / m 2 , thereby removing water, and the obtained laminated sheet of cellulose fibers and filter paper was dried at 110° C. for 1 hour. After drying, the cellulose fiber layer was peeled off from the filter paper to obtain a cellulose fiber sheet.

[0160] [Film appearance evaluation]

[0161] A portion of the obtained cellulose fiber sheet was cut out and vapor-deposited with osmium to prepare an observation sample, which was observed using an electron microscope at a magnification of 200 times.

[0162] Three locations were magnified using an electron microscope, and whether the porous structure of the surface was destroyed was evaluated according to the following evaluation criteria.

[0163] "×": Holes are crushed in almost all locations

[0164] "△": The hole is crushed in some places

[0165] "○": Holes are maintained in almost all locations.

[0166] Furthermore, whether or not coarse structures of 10 μm or more are present on the surface in a dry state was evaluated according to the following criteria.

[0167] “×”: Coarse structures are present in all 3 images

[0168] "△": Coarse structures are present in 1 or 2 of the 3 images

[0169] "0": No coarse structures are present in all 3 images.

[0170] [Measurement of air permeability resistance]

[0171] The obtained cellulose fiber sheet was measured for air permeability resistance (unit: sec / 100 cc) per 10 μm of film thickness in accordance with JIS-P8117. The sheet through which air did not pass was described as "unmeasurable".

[0172] [Preparation of cellulose fiber-rubber composite]

[0173] An aqueous suspension having a cellulose fiber concentration of 5.0% by weight relative to pure water was prepared, and natural rubber latex having a solid content concentration of 60.0% by weight was added at a weight ratio of natural rubber:cellulose fiber = 20:1. The obtained mixed solution was stirred with a rotary mixer, and the obtained wet masterbatch was thinly spread on a Teflon (registered trademark) plate, dried at 50°C for 48 hours, and further dried with a vacuum dryer for 3 hours to obtain a masterbatch.

[0174] The obtained masterbatch was pre-mixed at 50°C and 20 rpm for 5 minutes using LABO PLASTOMILL, and then added with a ratio of 0.5 g of stearic acid, 6.0 g of zinc oxide, 3.5 g of sulfur, and 0.7 g of vulcanization accelerator per 100 g of masterbatch, and further mixed at 50°C and 40 rpm for 10 minutes to obtain a block-shaped composite. The obtained composite was hot-pressed at 150°C and 30 MPa for 8 minutes using a heated oil press, and further cooled and pressed at 20°C and 10 MPa for 5 minutes to obtain a sheet-shaped cellulose fiber-rubber composite with a thickness of about 2 mm.

[0175] [Tensile test]

[0176] The obtained cellulose fiber-rubber composite was punched into a dumbbell shape, and the 100% stress (unit: MPa), tensile strength (unit: MPa), and elongation at break (unit: %) were measured according to JIS-K6215. As a blank for comparison, a rubber composition without cellulose fiber was prepared, and the 100% stress, tensile strength, and elongation at break were set to 1.00 for comparison. All tests were performed 5 times, and the average value was used as the test result.

[0177] [Evaluation of macroscopic structures on fracture surfaces]

[0178] The fracture surface after the tensile test was collected and osmium was vapor-deposited as an observation sample. The sample was observed with SEM-EDX at a magnification of 500 times, and mapped with carbon atoms and oxygen atoms. The following evaluation criteria were used to evaluate whether there were coarse structures of 10 μm or more in the dry state on the fracture surface.

[0179] “×”: All 5 images contain coarse structures

[0180] "△": Coarse structures are present in 1 to 4 out of 5 images

[0181] "0": No coarse structures were present in all 5 images.

[0182] [Marine biodegradability assessment]

[0183] The obtained cellulose fibers were placed in seawater with reference to ASTM D6691, and the amount of oxygen consumed during cellulose degradation was measured for 28 days to evaluate the degradation rate. The degradation rate of microcrystalline cellulose as a reference substance was evaluated in parallel at the same timing. After 28 days, if more than 90% degradation was shown in comparison with the reference substance, it was judged to have sufficient marine biodegradation rate. Both cellulose fibers and reference substances were evaluated with n=2, and the average value was used as the result.

[0184] [Preparation of cellulose fibers]

[0185] [Example 1]

[0186] Cotton linter pulp was dissolved in a copper ammonia solution to prepare a copper ammonia cellulose solution having a cellulose concentration of 5.0 wt %, a copper concentration of 1.8 wt %, and an ammonia concentration of 5.5 wt %, and the solution was filtered through a sintered filter having an average pore size of 5 μm to remove foreign matter.

[0187] As a spinning nozzle, a copper ammonia cellulose solution was ejected in 20°C warm water from a spinneret having an ejection hole with a hole diameter of 0.3 mm, a number of holes of 180, and a hole-to-hole distance of 1.1 mm, and stretched and deaminated by a downward tension spinning method to produce a raw yarn, and while 50°C warm water was flowing in a semicircular inclined groove set 20 cm below the funnel outlet, the raw yarn and the warm water were received and injected into a plastic mesh, thereby separating the raw yarn and the warm water. 10% by weight sulfuric acid was injected into the raw yarn by spraying to fully remove copper, and then pure water was sprayed to fully wash the sulfuric acid to obtain a continuous cellulose fiber in a wet state.

[0188] The obtained continuous cellulose fibers were diluted in pure water to prepare an aqueous suspension having a cellulose concentration of 1.0 wt %. 500 ml of the suspension was added to a mixer (X-TREME MILL, MX-1200XT manufactured by AS ONE Corporation) and treated for 5 minutes to prepare short-fibered cellulose fibers.

[0189] [Example 2]

[0190] Stapled cellulose fibers were prepared in the same manner as in Example 1 except that the ammonia concentration of the cuprammonium cellulose solution was 8.0% by weight.

[0191] [Example 3]

[0192] Stapled cellulose fibers were prepared in the same manner as in Example 2 except that the cellulose concentration of the cuprammonium cellulose solution was 4.0% by weight and the copper concentration was 1.4% by weight.

[0193] [Example 4]

[0194] Stapled cellulose fibers were prepared in the same manner as in Example 1 except that the ammonia concentration of the cuprammonium cellulose solution was 4.5% by weight.

[0195] [Example 5]

[0196] Stapled cellulose fibers were prepared in the same manner as in Example 4 except that the cellulose concentration of the cuprammonium cellulose solution was 7.0% by weight and the copper concentration was 2.5% by weight.

[0197] [Example 6]

[0198] The short-fibered cellulose fibers obtained in Example 1 were subjected to a micronization treatment five times at an operating pressure of 100 MPa using a high-pressure homogenizer (NS015H manufactured by NIA SOLOBI CO., LTD.) to prepare short-fibered cellulose fibers.

[0199] [Example 7]

[0200] The short-fibered cellulose fibers obtained in Example 1 were suspended in 10% by weight sulfuric acid in a manner such that the cellulose concentration was 0.1% by weight, heated to 70° C. and stirred with a magnetic stirrer for 30 minutes, and the sulfuric acid was washed with pure water to obtain cellulose fibers that were easily fibrillated. The obtained cellulose fibers were treated with a high-pressure homogenizer in the same manner as in Example 7 to prepare short-fibered cellulose fibers.

[0201] [Example 8]

[0202] The cuprammonium cellulose solution was set to a cellulose concentration of 7.0 wt% and a copper concentration of 2.5 wt%, and stirred overnight in an oxygen atmosphere to reduce the degree of polymerization of cellulose. Continuous cellulose fibers were prepared in the same manner as in Example 1, and then micronized using a high-pressure homogenizer in the same manner as in Example 6 to prepare short-fibered cellulose fibers.

[0203] [Example 9]

[0204] As a spinning nozzle, a spinneret having a jet hole with a hole diameter of 0.3 mm, a number of holes of 800, and a hole spacing of 1.1 mm was used. The original yarn coming out of the funnel outlet was deflected, and warm water of 50° C. was applied. The speed was adjusted by a roller to form a state in which the tension of the original yarn was reduced. 10% by weight of sulfuric acid was dripped onto the original yarn running in the horizontal direction by the nozzle to remove copper. Then, the yarn was immersed in a bath of pure water flowing along the convection to wash sulfuric acid, thereby obtaining cellulose fibers wound into a bobbin. The obtained cellulose fibers wound into a bobbin were cut using a rotary cutter in which a plurality of cutting blades were arranged radially at a pitch of 1 mm to prepare short-fibered cellulose fibers.

[0205] It should be noted that when the original yarn that changed direction and ran in the lateral direction was touched with a fingertip, the surface of the yarn was smooth, indicating that the single yarns were not firmly bonded to each other.

[0206] [Example 10]

[0207] The short-fiber cellulose fibers obtained in Example 9 were treated with a high-pressure homogenizer in the same manner as in Example 6 to prepare short-fiber cellulose fibers.

[0208] [Example 11]

[0209] The short-fibered cellulose fibers obtained in Example 2 were subjected to a refining treatment five times at an operating pressure of 50 MPa using a high-pressure homogenizer (NS015H manufactured by NIA SOLOBI CO., LTD.) to prepare short-fibered cellulose fibers.

[0210] [Comparative Example 1]

[0211] With reference to Patent Document 6, a cellulose copper-ammonia solution having a cellulose concentration of 8.0 wt%, a copper concentration of 2.9 wt%, and an ammonia concentration of 7.0 wt% was prepared, and downward tension spinning was performed using a spinneret having ejection holes with a pore size of 0.6 mm, a number of holes of 2430, and a distance between holes of 1.4 mm to form filaments. The filaments exiting the funnel outlet were redirected and regenerated with sulfuric acid using a scouring bath in a rectifying state in the same direction as the filaments. Thereafter, the sulfuric acid was washed off the mesh in the same manner as in Example 1, and the cellulose fibers were stapled using a mixer to prepare stapled cellulose fibers.

[0212] It should be noted that when the original yarn that changed direction and ran in the lateral direction was touched with a fingertip, it had an uneven touch, unlike Example 9, suggesting that the single yarns were firmly bonded to each other.

[0213] [Comparative Example 2]

[0214] The cellulose fibers obtained in Comparative Example 1 were treated with a high-pressure homogenizer in the same manner as in Example 6 to prepare short-fiber cellulose fibers.

[0215] [Comparative Example 3]

[0216] Stapled cellulose fibers were prepared in the same manner as in Comparative Example 1 except that the cellulose concentration of the cuprammonium cellulose solution was 10.0% by weight and the copper concentration was 3.6% by weight.

[0217] [Comparative Example 4]

[0218] With reference to Patent Document 7, a cellulose copper ammonia solution having a cellulose concentration of 3.5 wt%, a copper concentration of 1.3 wt%, an ammonia concentration of 18.0 wt%, a PEG500000 concentration of 0.5 wt%, and a polyoxyethylene lauryl ether concentration of 0.1 wt% was prepared, and filtered with a sintered filter having an average pore size of 5 μm to remove foreign matter. Electrospinning was performed using a metal nozzle having an inner diameter of 0.41 mm, and copper removal was performed with sulfuric acid. The cellulose fibers were separated from the collector, and the sulfuric acid, PEG, and surfactant were washed with pure water. The fibers were short-fibered using a mixer in the same manner as in Example 1 to prepare short-fibered cellulose fibers.

[0219] [Comparative Example 5]

[0220] General cellulose nanofibers (biomass nanofiber "BiNFi-s" WFo-100 manufactured by SUGINO MACHINE LIMITED) were used.

[0221] [Comparative Example 6]

[0222] Cotton linter pulp was used as a cellulose raw material, and alkali treatment was performed with a caustic soda aqueous solution with pH = 13 before micronization. Micronization was performed five times using a high-pressure homogenizer (NS015H manufactured by NIA SOLOBI CO., LTD.) at an operating pressure of 100 MPa to prepare short-fiber cellulose fibers.

[0223] [Comparative Example 7]

[0224] Stapled cellulose fibers were prepared in the same manner as in Comparative Example 6 except that the operating pressure of the high-pressure homogenizer was changed to 50 MPa.

[0225] [Comparative Example 8]

[0226] Referring to Patent Document 8, a pore size of 0.07 mm, a number of pores of 2430, and a distance between pores of 0.67 mm (equivalent to a pore density of 180.9 pores / cm 2 ) was used, a copper ammonia cellulose solution was ejected in warm water at 20°C, and a raw yarn was prepared by stretching and deammoniation by a downward tension spinning method, and a plastic mesh was used to receive the raw yarn and spinning water. The short-fibered cellulose fibers were prepared in the same manner as in Example 1. It should be noted that when the situation in the funnel was observed, the yarns were in contact with each other due to the shaking of the yarns, suggesting that the fibers were in a state of aggregation.

[0227] [Evaluation of cellulose fiber]

[0228] SEM observation and optical automatic analysis were performed on the cellulose fibers of Examples 1 to 11 and Comparative Examples 1 to 8. It should be noted that the proportion of coarse structures with a fiber diameter of 0.1 μm or less measured in a dry state in Comparative Example 5 was 99%, and the proportion of coarse structures with a Wet fiber diameter of 20 μm or more measured in a wet state was 1.4%. This is because, although the total exceeds 100%, in the measurement of a very small part magnified by an electron microscope, the coarse structures are sometimes not included in the measurement field. In addition, fibers that appear to be independent in the image of a very small part magnified are sometimes connected in the invisible part of the image. The average fiber diameter of the fibers of Comparative Example 5 is less than 0.3 μm, so the result of the optical automatic analysis is recorded as a reference value with an * mark in the upper right of the numerical value. In Example 1, Example 6, Comparative Example 1, and Comparative Examples 4 to 7, X-ray diffraction measurement was performed. The SEM images of Example 1, Comparative Example 1, Comparative Example 4, Comparative Example 7, and Comparative Example 8 are shown in the table below, respectively. Figure 1 , Figure 2 , Figure 8 , Figure 3 , Fig. 9 The evaluation results are summarized in Table 1 below.

[0229] [Table 1]

[0230]

[0231] Depend on Figures 1 to 3 , 8, 9 and Table 1 show that the cellulose fibers obtained in Examples 1 to 10 are microfibers in terms of average fiber diameter, but the proportion of nanofibers is small, so the fiber diameter aggregation constant is small and the fiber is highly stable. Furthermore, the proportion of coarse structures is also small, and the fiber diameter is uniform with a small coefficient of variation. In addition, as in Examples 1 to 5, the fiber diameter can be freely controlled by adjusting the spinning conditions, and as in Examples 6 to 10, the fiber length can be freely controlled while maintaining the fiber diameter by adjusting the micronization conditions.

[0232] In contrast, even if the same wet spinning method is used, there is a certain amount of coarse structures in the fibers of Comparative Examples 1, 4, and 8 obtained by the existing spinning method. In the cellulose fibers of Comparative Example 1, the cellulose fibers are firmly bonded to each other at the stage just after spinning. As in Comparative Example 2, even if the crushing treatment is performed, a certain amount of coarse structures remain, and nanofibers are generated due to fibrillation. The cellulose fibers of Comparative Example 8 are also firmly bonded to each other at the stage just after spinning, just like Comparative Example 1. In addition, in the cellulose fibers of Comparative Example 4, as long as SEM is observed, it is impossible to determine whether the fibers are firmly bonded to each other, and only a very small amount of granular parts with a diameter of more than 3μm can be seen in the field of view, but if evaluated by optical automatic analysis, there is a certain amount of coarse structures. In addition, as in Comparative Examples 5 to 7, in the fibers obtained by physically or chemically refining natural cellulose, there is a certain amount of nanofibrillated parts and coarse structures.

[0233] [Performance evaluation as filter substrate]

[0234] Using the cellulose fibers obtained in Examples 1 to 6 and Comparative Examples 4 to 7, a cellulose fiber having a unit area weight of 40 g / m 2 The cellulose fiber sheets obtained in Example 1, Comparative Example 4, and Comparative Example 7 were evaluated as filter substrates. SEM images of the cellulose fiber sheets obtained in Example 1, Comparative Example 4, and Comparative Example 7 are shown in FIG. Figure 4 , Fig.10 , Figure 5 The evaluation results are summarized in the following figures.

[0235] [Table 2]

[0236]

[0237] Depend on Figure 4 and 5It can be seen that in the cellulose fibers of Example 1, even if they are dried by heat drying, the gaps between the fibers are maintained, and a uniform porous sheet is obtained. In contrast, in the cellulose fibers of Comparative Example 7, nanofibers are present, the fiber length is short, and the gaps between the fibers are filled due to shrinkage during drying, and the obtained sheet does not have a uniform porous structure.

[0238] Furthermore, it can be seen from Table 2 that in the sheets prepared from cellulose fibers having a high proportion of nanofibers obtained in Comparative Examples 5 and 6, the gaps between the fibers are filled to the extent that the air permeability resistance cannot be measured, and it cannot be said that the structure is porous. In addition, in the cellulose fibers of Comparative Examples 5 and 6 having shorter fiber lengths, the interweaving of the fibers is untied during drying, and the gaps between the fibers are easily filled. Fig.10 It is understood that the sheets prepared from the cellulose fibers of Comparative Examples 4 and 7, which have many coarse structures, contain coarse structures in the sheets and are prone to defects such as pinholes and reduced strength.

[0239] [Evaluation of performance as filler in rubber composition 1]

[0240] Cellulose fiber-rubber composites were prepared using the cellulose fibers obtained in Examples 1 to 8 and 11 and Comparative Examples 4 to 7, and evaluated as fillers. The SEM-EDX images of the fracture surfaces of Example 1 and Comparative Example 6 are shown in FIG. Figure 6 , Figure 7 The evaluation results are summarized in Table 3 below.

[0241] [Table 3]

[0242]

[0243] Depend on Figure 6 and 7 It is found that the cellulose fibers on the fracture surface of the cellulose fiber-rubber composite obtained from the cellulose fibers of Example 1 are well dispersed, whereas the fracture surface of the composite obtained from the cellulose fibers of Comparative Example 6 having coarse structures has lumps of cellulose everywhere.

[0244] Furthermore, as can be seen from Table 3, the elongation at break of the cellulose fiber-rubber composite obtained from the cellulose fibers of Examples 1 to 8 and 11 is not reduced, the tensile strength is improved, and the fiber length is constant, so the 100% stress can be improved in the same manner as the compounding agent containing type I cellulose. On the other hand, the elongation at break of the composite obtained from the cellulose fibers containing coarse structures of Comparative Examples 4 to 7 is easily reduced, which easily causes a reduction in tensile strength.

[0245] [Evaluation of performance as filler in rubber composition 2]

[0246] The cellulose fibers obtained in Example 1 were used to prepare cellulose fiber-rubber composites by changing the amount of cellulose fibers relative to rubber to 3 wt% and 10 wt%, and the composites were evaluated as fillers. The SEM-EDX images of the fracture surfaces of Examples 1-3 are shown in FIG. Fig.11 The evaluation results are summarized in Table 4 below.

[0247] [Table 4]

[0248]

Table 4

[0249]

[0250] Depend on Fig.11 It is known that the cellulose fibers of Example 1 can maintain good dispersion of the cellulose fibers even when the blending amount is increased. Also, as shown in Table 4, the tensile strength can be maintained even when 10 wt% of the cellulose fibers are blended, and the 100% stress is improved depending on the blending amount.

[0251] [Evaluation of marine biodegradability]

[0252] The marine biodegradability was evaluated using the cellulose fibers obtained in Example 1. The degradation degree after 28 days was 93% compared to the reference substance, and it was confirmed that the biodegradation in the ocean was sufficiently rapid.

[0253] Industrial Applicability

[0254] The cellulose fiber of the present invention is a uniform cellulose microfiber (fibrous cellulose aggregate) with few coarse structures without the addition of chemical substances or modification of cellulose, and can be generally used in various applications such as fillers for reinforcing resins and rubbers, and base materials for porous bodies such as filters. In addition, the cellulose fiber of the present invention can also be suitably used for materials for porous bodies such as adsorbents, sound absorbing materials, and heat insulating materials, transparent materials for electronic products, base materials for optical materials, additives for foods, coatings, and cosmetics, packaging materials, base materials for gas barrier materials, viscosity modifiers for liquid products, dispersion stabilizers, base materials for artificial leather, and clothing applications using synthetic fibers and cellulose fibers.

Claims

1. A cellulose fiber, wherein The average fiber diameter in the dry state observed by electron microscope is greater than 0.3 μm and less than 3.0 μm, the proportion of fibers with a fiber diameter less than 0.1 μm is less than 5%, and the proportion of coarse structures is less than 3.0%, and the proportion of coarse structures is measured by the ratio of the number of fibers with a wet fiber diameter of more than 20 μm measured by optical automatic analysis.

2. The cellulose fiber according to claim 1, wherein The wet average fiber diameter is 1.0 μm or more and less than 10.0 μm.

3. The cellulose fiber according to claim 1 or 2, wherein The wet average fiber length is less than 3000 μm.

4. The cellulose fiber according to claim 1 or 2, wherein The coefficient of variation of the fiber diameter is 1.00 or less.

5. The cellulose fiber according to claim 1 or 2, wherein The aggregation constant of the fiber diameter is 5.0 or less.

6. The cellulose fiber according to claim 1 or 2, wherein The crystal structure of cellulose constituting cellulose fibers is type II.

7. The cellulose fiber according to claim 1 or 2, wherein The crystallinity of cellulose constituting the cellulose fibers is 30% or more and 90% or less.

8. A composition comprising the cellulose fiber according to claim 1 or 2. 9 . A porous body formed from the cellulose fibers according to claim 1 .

Citation Information

Patent Citations

  • JP1973071196A

  • Warpers beam lifting and conveying cart

    JP1980084445A

  • Filler / rubber composite

    JP2020055951A

  • Cellulose fiber aqueous dispersion

    JP2020125417A

  • Composite material

    JP2021014512A